Comparison of Laboratory Data of Acute Cholangitis Patients Treated with or without Immunosuppressive Drugs. (10th March 2014) - Tomizawa, Minoru; Shinozaki, Fuminobu; Hasegawa, Rumiko; Shirai, Yoshinori; Ichiki, Noboru; Motoyoshi, Yasufumi; Sugiyama, Takao; Yamamoto, Shigenori; Sueishi, Makoto
Abstract : Objective. Symptoms and laboratory data between acute cholangitis (AC) patients treated with and AC patients treated without immunosuppressive drugs (corticosteroids or methotrexate) were compared to identify factors that can be meaningful to the diagnosis of AC. Methods. The Wilcoxon signed-rank test was used for comparison of baseline variables between the patients with AC treated with immunosuppressive drugs and those without it. The chi-squared test was used in the analysis of the symptoms. Results. In total, 69 patients with AC were enrolled. Fifteen patients were treated with immunosuppressants due to rheumatoid arthritis or other collagen diseases. Jaundice was less frequent in the patients treated with immunosuppressive drugs (P   =   0.0351 ). T-Bil level was marginally lower in the patients treated with immunosuppressants (P   =   0.086 ). AST and ALT levels were lower in the patients treated with immunosuppressants (P   =   0.0417 and 0.022, respectively). Conclusions. The frequency of jaundice and AST and ALT levels were lower in the patients treated with immunosuppressive drugs. It is recommended that care be taken to evaluate jaundice, AST level, and ALT level in the diagnosis of AC.